Bargaining and Time Preferences: An Experimental Study - Jeongbin Kim; Wooyoung Lim; Sebastian Schweighofer-Kodritsch (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We generalize the Rubinstein (1982) bargaining model by disentangling payoff delay from bargaining delay. We show that our extension is isomorphic to generalized discounting with dynamic consistency and characterize the unique equilibrium. Using a novel experimental design to control for various confounds, we then test comparative statics predictions with respect to time discounting. All bargaining takes place within a single experimental session, so bargaining delay is negligible and dynamic consistency holds by design, while payoff delay per disagreement round is significant and randomized transparently at the individual level (week/month, with/without front-end delay). In contrast to prior experiments, we obtain strong behavioral support for the basic predictions that hold regardless of the details of discounting. Testing differential predictions of different forms of discounting, we strongly reject exponential discounting in favor of present-biased discounting.
Keywords: C78; C91; D03; 330; alternating-offers bargaining; time preferences; present bias; laboratory experiments